THE APPLICATION OF THE EXAMPLE NON EXAMPLE LEARNING MODEL TO THE STUDENTS' IPA LEARNING OUTCOMES FOR CLASS V - Sartika, Leni; Satinem, Yohana; Yuneti, Armi (Universitas Trunojoyo Madura, 2022)
This study aims to determine the completion of science learning outcomes for fifth grade students of SD Negeri 2 Air Satan.The research method used is in the form of a quasi-experimental. The population is all fifth grade students of SD Negeri 2 Air Satan and the research sample is 14 students. Data was collected by using saturated sampling technique. The data collected through the test was then analyzed using the z test. Based on the results of data analysis with a confidence level = 5% and dk = 13, it shows that zcount = 2.89 and ztable = 1.64 (zcount ztable). Thus, it can be concluded that the science learning outcomes of fifth grade students of SD Negeri 2 Air Satan after the implementation of the non-example ecample learning model were significantly completed.